Safety and Non-Inferiority Evaluation of Two Immunization Schedules with an Inactivated SARS-CoV-2 Vaccine in Adults: A Randomized Clinical Trial - Katia Abarca; Carolina Iturriaga; Marcela Urzúa; Nicole Le Corre; Augusto Pineda; Carolina Fernández; Angélica Domínguez; Pablo A. González; Susan M. Bueno; Paulina Donato; Pilar Espinoza; Daniela Fuentes; et al. (Vaccines, 2022)
Several vaccines have been developed to control the COVID-19 pandemic. CoronaVac®, an inactivated SARS-CoV-2 vaccine, has demonstrated safety and immunogenicity, preventing severe COVID-19 cases. We investigate the safety and non-inferiority of two immunization schedules of CoronaVac® in a non-inferiority trial in healthy adults. A total of 2302 healthy adults were enrolled at 8 centers in Chile and randomly assigned to two vaccination schedules, receiving two doses with either 14 or 28 days between each. The primary safety and efficacy endpoints were solicited adverse events (AEs) within 7 days of each dose, and comparing the number of cases of SARS-CoV-2 infection 14 days after the second dose between the schedules, respectively. The most frequent local AE was pain at the injection site, which was less frequent in participants aged ≥60 years. Other local AEs were reported in less than 5% of participants. The most frequent systemic AEs were headache, fatigue, and myalgia. Most AEs were mild and transient. There were no significant differences for local and systemic AEs between schedules. A total of 58 COVID-19 cases were confirmed, and all but 2 of them were mild. No differences were observed in the proportion of COVID-19 cases between schedules. CoronaVac® is safe, especially in ≥60-year-old participants. Both schedules protected against COVID-19 hospitalization.